Two-dimensional photonic crystals as perspective materials of modern nanoelectronics - Karachevtseva, L.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Photonic crystals are a dynamic direction of modern solid state physics. Today the intensive research (more than 80 %) is concentrated on two-dimensional photonic crystals which have functionality of three-dimensional photonic crystals and rather simple manufacturing techniques and is directed towards the development of active and passive elements of the future integrated nanophotonic circuits. Twodimensional photonic macroporous silicon structures are perspective for development of photonic waveguides, thermal receivers due to occurrence of the powerful absorption bands in the infrared spectrum range. Formation macroporous silicon structures with nanocoatings expands its functionalities as photodetectors and light emitters.